2018
DOI: 10.30813/psibernetika.v10i1.1037
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Budaya Individualis-Kolektif Dan Motivasi Berbelanja Hedonik Pada Masyarakat Kota Jakarta

Abstract: <p><em>Many shopping centers try to create an environment that makes consumers feel comfortable when they do shopping. Hedonic shopping motivation relates to contentment and enjoyment by shopping experience, it creates happiness feeling. Hedonic shopping motivation can not be separated from the role of culture in the society. This research aimed to know the relationship between individualist-collective culture with hedonic shopping motivation among people in Jakarta. The research used non ecperimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
3
0
3
Order By: Relevance
“…In Figure 4 shows that the culture from "Gotong Royong" clearly illustrates that both the internal and external workers hold discussions together. The collective values displayed shows that the Indonesian community accept, take care of each other, and move towards a common interest (Jatmika, 2018). In this scene, it can be concluded that GoTo wants to emphasize the concept of cooperation between each other and achieving success in the future.…”
Section: Resultsmentioning
confidence: 95%
“…In Figure 4 shows that the culture from "Gotong Royong" clearly illustrates that both the internal and external workers hold discussions together. The collective values displayed shows that the Indonesian community accept, take care of each other, and move towards a common interest (Jatmika, 2018). In this scene, it can be concluded that GoTo wants to emphasize the concept of cooperation between each other and achieving success in the future.…”
Section: Resultsmentioning
confidence: 95%
“…Indonesia merupakan negara dengan budaya kolektivis dan mempunyai nilai yang cukup rendah pada indeks individualis di dunia (Hofstede et al, 2005). Dengan masyarakat yang kolektivis, setiap orang merupakan bagian dari kelompok tersebut dan saling menjaga serta diharapkan mengikuti harapan masyarakat atau kelompoknya (Jatmika, 2017).…”
Section: Pembahasan Dan Kesimpulanunclassified
“…Budaya memberikan dampak yang cukup banyak pada setiap individu dalam perkembangan dan pertumbuhannya yang belajar dari lingkungan sekitarnya. Hal ini berhubungan juga dengan individu yang tumbuh dan berkembang di lingkungan yang kolektivis, ia akan mementingkan kepentingan kelompoknya dan perilaku mereka diatur oleh norma sosial dibandingkan dari sikap pribadinya (Jatmika, 2017).…”
Section: Pembahasan Dan Kesimpulanunclassified
“…Berdasarkan penelitian yang dilakukan Soliha (2015) di Indonesia pola interaksi dari sisi kolektif sudah mulai berubah ke sisi individualis. Individu dengan pola interaksi individualis lebih memperdulikan dirinya sendiri, lebih fokus dengan pada tujuan personal dibandingkan kelompok, dan berperilaku sesuai dengan sikap individu dari pada norma masyarakat (Jatmika, 2017).…”
Section: Gambar 1 Mediating Effect Frameworkunclassified